Field studies on thermal comfort of air-conditioned and non air-conditioned buildings in Malaysia - Hussein I.; Rahman M.H.A.; Maria T. (2023)
Field studies on the environmental conditions and occupant comfort were carried out in air-conditioned buildings and non air-conditioned buildings in Malaysia. The study on the air-conditioned buildings was carried out in UNITEN and for the non air-conditioned buildings in two schools, which is a primary and secondary school, and in a public waiting area in a health clinic in Johor Bahru, located in the southern region of Malaysia. The non air-conditioned buildings were mechanically ventilated by fans. The studies were made in different days from morning until noon as to get variation of temperatures, collecting a full set of objective physical measurements and subjective assessments through questionnaires. The measured environmental parameters were air temperature, relative humidity and air velocity. The subjective responses concern the judgment of the respondents about the thermal environment at the moment of measurements. The results obtained showed that majority of the respondents found that their indoor thermal conditions acceptable even though most of the thermal sensation votes (TSV) exceeded those specified by ASHRAE Standard 55 and the environmental assessments exceeded the standard. The neutral temperature and comfort range were obtained through linear regression analysis of TSV and in the Fanger's PMV model. From the subjective assessment, it was found that the occupants can accept the thermal range beyond the ASHRAE comfort zone. The neutral temperature of 24.4C and 28.4C for air-conditioned and non air-conditioned buildings respectively, were obtained by regression analysis of TSV on operative temperature. The acceptable range of temperature obtained by regression analysis of TSV were 23.1C to 25.6C for air-conditioned buildings and 26.0oC to 30.7C for non air-conditioned buildings. 2009 IEEE.